Job Demands, Engagement, and Turnover Intentions in Polish Nurses: The Role of Work-Family Interface - Dåderman, Anna M.; Basinska, Beata A. (Frontiers in Psychology, 2016)
Background: Poland has lower ratios of employed registered nurses per 1,000 inhabitants than the EU average. Polish nurses work under miserable conditions without assisting personnel, and they reconcile their professional demands with responsibilities for their families; 96% of them are women. Rationale/Aims: This study uses Hobfoll’s Conservation of Resources (COR) theory to explain the role of various resources in the improvement of work conditions in the nursing profession. Work-family conflict (WFC) and family-work conflict (FWC) threaten to deplete nurses’ resources. This paper set out to (1) examine the extent to which perceived job demands (workload and interpersonal conflicts at work) and engagement (vigour, dedication and absorption) are associated with turnover intentions (the intention to leave the present workplace and the intention to leave the nursing profession); (2) attempt to determine whether levels of WFC and FWC moderate these associations. Design/Method: This study comprised 188 female registered nurses. The inclusion criterion was to live with a partner and/or have children. Results: WFC was moderately related to FWC. Hierarchical regression analyses showed that only high job demands and low vigour were significantly associated with turnover intentions. WFC was experienced more intensively than FWC. Job demands, vigour, dedication and turnover intentions had a strong effect on WFC, while absorption had a strong effect on FWC. However, levels of WFC and FWC did not significantly moderate these associations. Originality/Conclusion: The study produces new knowledge by examining a constellation of job demands, work engagement and WFC, which reflect the management of personal resources. Results from such a constellation in nurses from countries with a post-transformational economic system have not previously been discussed in the light of COR theory. Most importantly, we conclude that WFC does not intensify turnover intentions.